SYMBOL OF THE TRINITY IN THE RUSSIAN PHILOSOPHICAL UTOPIA (DM. MEREZHKOVSKY AND D. ANDREEV) - N. G. Mitina (Концепт: философия, религия, культура, 2018)
The article considers the changes in social religious foundations proposed by utopian projects of Russian philosophy, focusing on the tenet of the Trinity interpretation. For analysis, two utopias were selected («Third Kingdom» of Dm. Merezhkovsky and D.A. Andreev’s «Rose of Peace»), with special attention paid to changing the religious foundations of the future society.The project of Dm. Merezhkovsky was created within the framework of the «new religious consciousness» concept that took shape in the philosophy of the Silver Century. The union of religion and culture through the spiritual rebirth of a man in a new society is important for the philosopher. The main goal of the project is the Kingdom of God, where the evolution of Christianity took place, a single world church was created, the secret of sex was revealed and the harmony of nature and society was established. His religion of the «Third Testament» should resolve all existing contradictions. Appeal to the symbolism gives him the opportunity to reveal the significance of the religious tenet about the Trinity. In this utopia, feminine plays a leading role, which makes it possible to trace the connection with feminist projects of the XXth century.D. Andreev’s utopia “Rose of the World”, as well as the project of Dm. Merezhkovsky, is built on new religious teachings of the philosopher, called interreligious by him. The ultimate goal is the World Brotherhood, reminiscent of the ideal of the Kingdom of God. It is also based on the retreatment of the tenet of the Trinity - the introduction of the Female Deity. In the Divine, thus, the polarity of two principles - male and female - manifests itself. The philosopher examines the role of the feminine and the masculine and concludes about the need of their relative balance in the world.We see two projects offering their vision of religious ideas in the future society, built on Yin-Yang Balance in the world. Philosophers show the importance of the feminine principle, its role in the harmonization of society through the interpretation of the Trinity.